Home Baking Business Analysis Using the Canvas Business Model for Mekaar Customers at PT Permodalan Nasional Madani, Bandung Branch - Sumawinata; A. Dewantoro Marsono (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to map, evaluate and improve the culinary business model for customers of PNM Mekaar Bandung Branch. This study uses a qualitative method with data collection tools through in-depth interviews to obtain information and analyze the business model. The research subjects were the customers of PNM Mekaar Bandung Branch. The results of the study show that culinary business actors carried out by customers of PNM Mekaar Bandung Branch have not fully used the Business Model Canvas. Of the nine elements of the Business Model Canvas, only five blocks were given additional for improvement as a future business development effort, namely: Customer Segments, Value Propositions, Channels, Customer Relationships, and Key Partnerships. Strategy with the Business Model Canvas can be effective and efficient in determining company strategy